Study on Analysis of Peripheral Biomarkers for Alzheimer’s Disease Diagnosis - Rani, Palaniswamy; Krishnan, Sreeram; Rani Cathrine, Chellappa (Frontiers in Neurology, 2017)
Many factors are involved in Alzheimer’s disease (AD) pathology including tau phosphorylation, amyloid β protein (Aβ) accumulation, lipid dysregulation, oxidative stress and inflammation. The markers of these pathological processes in cerebral spinal fluid CSF are used currently for AD diagnosis. However peripheral biomarkers are the need of the hour for large population screening for AD. The main objective of the present study is to evaluate the peripheral levels of redox markers, lipid peroxidation indicators and pathological markers in AD patients. Blood was collected from AD patients (n=45), controls (n=45) and analyzed for pathological markers of AD including Aβ42 and tau, lipid peroxidation and redox indicators. Plasma Aβ42 was significantly (P<0.001) elevated while total tau was decreased in AD compared to controls. Hydroxynonenal (HNE) and Malondialdehyde (MDA), were higher (P<0.001) in AD patients pointing the enhanced lipid peroxidation in AD pathology. Receiver operating characteristic curve (ROC) analysis indicated that HNE is a better indicator of lipid peroxidation compared to MDA. Plasma glutathione (GSH) level was significantly (P<0.001) low while oxidized glutathione (GSSG) level was higher (P<0.001) in AD patients with corresponding decrease in GSH/GSSG ratio (P<0.001). ROC analysis indicated that GSH/GSSG ratio can be used as reliable indicator for redox imbalance in AD with a cutoff value of <8.73 (Sensitivity 91.1%, Specificity 97.8%). Correlation analysis revealed a positive correlation for both HNE and MDA with Aβ42 and a negative correlation with total tau. Negative correlation was observed between GSH/GSSG ratio and lipid peroxidation markers. While oxidative stress has been implicated in pathology of various neurodegenerative disorders, the present study pinpoints the direct link between lipid peroxidation and Aβ production in plasma of AD patients. Normally at low amyloid concentration in body fluids, this peptide shown to function as a strong metal chelating antioxidant. However when the Aβ production enhanced as in AD, through gain of functional transformation, Aβ evolves into prooxidant thereby enhancing oxidative stress and LPO. Altered redox status with enhanced lipid peroxidation observed in AD blood could contribute to the oxidation and S –Glutathionylation proteins which has to be addressed in future studies.